Physiological phenotyping of dementias using emotional sounds. Issue 2 (22nd April 2015) - Fletcher, Phillip D.; Nicholas, Jennifer M.; Shakespeare, Timothy J.; Downey, Laura E.; Golden, Hannah L.; Agustus, Jennifer L.; Clark, Camilla N.; Mummery, Catherine J.; Schott, Jonathan M.; Crutch, Sebastian J.; Warren, Jason D.
Abstract: Introduction: Emotional behavioral disturbances are hallmarks of many dementias but their pathophysiology is poorly understood. Here we addressed this issue using the paradigm of emotionally salient sounds. Methods: Pupil responses and affective valence ratings for nonverbal sounds of varying emotional salience were assessed in patients with behavioral variant frontotemporal dementia (bvFTD) (n = 14), semantic dementia (SD) (n = 10), progressive nonfluent aphasia (PNFA) (n = 12), and AD (n = 10) versus healthy age‐matched individuals (n = 26). Results: Referenced to healthy individuals, overall autonomic reactivity to sound was normal in Alzheimer's disease (AD) but reduced in other syndromes. Patients with bvFTD, SD, and AD showed altered coupling between pupillary and affective behavioral responses to emotionally salient sounds. Discussion: Emotional sounds are a useful model system for analyzing how dementias affect the processing of salient environmental signals, with implications for defining pathophysiological mechanisms and novel biomarker development.